Exploring the antecedents of entrepreneurship success in information technology firms in Nigeria. (3rd April 2021) - Okeremi, Akinyele; Amoako-Gyampah, Kwasi; Divine Caesar, Livingstone
ABSTRACT: We examine four antecedents of IT entrepreneurship success in Nigeria. Particularly, two of the investigated antecedents are general human capital factors (i.e., having experience with entrepreneurial parents and business training) and the other two (IT education and spirituality) are specific to IT entrepreneurship and the Nigerian context. In a quantitative study of 167 IT entrepreneurs in Nigeria, we found that the general factors are more important determinants of success among IT entrepreneurs in Nigeria than the specific ones. There is corroboration between our findings and the developed economy literature which provides ample evidence of a positive relationship between having experience with entrepreneurial parents and entrepreneurship success. Before our findings, limited knowledge existed on the complexity of this orthodoxy in developing markets such as Nigeria. Our result did not show any significant correlation between formal education in the IT field and IT entrepreneurial success. Our paper contributes to the discourse on the antecedents of entrepreneurship success by focusing on IT entrepreneurship from a developing country context. This is particularly critical when one considers the importance of IT entrepreneurship towards economic diversification in Nigeria. The unique theoretical contribution of our paper lies in its introduction of the specific antecedents (constructs), IT-education and spirituality, even though they were not found as significant determinants of entrepreneurship success in the Nigerian context. Our findings imply that national entrepreneurial policy should be tailored to exploit the inherent benefits of experience with entrepreneurial parents and effectively blend it with factors such as business school education and other forms of relevant training in the areas of social competence.